2015
DOI: 10.1111/apa.13270
|View full text |Cite|
|
Sign up to set email alerts
|

Functional gastro‐intestinal disorder algorithms focus on early recognition, parental reassurance and nutritional strategies

Abstract: Up to 50% of infants present with symptoms of regurgitation, infantile colic and, or, constipation during the first 12 months of life. Although they are often classed as functional disorders, there is an overlap with cows' milk allergy. We present practical algorithms for the management of such disorders, based on existing evidence and general consensus, with a particular focus on primary healthcare. Management consists of early recognition of warning signs of organic disease, parental reassurance and nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(108 citation statements)
references
References 59 publications
4
93
0
11
Order By: Relevance
“…The aim of this study was to evaluate the efficacy of a formula containing a partially hydrolyzed whey protein (pWH), reduced lactose content, the probiotic Bifidobacterium lactis BB12 and the prebiotic galacto-oligosaccharide (GOS) in formula fed infants suffering from IC. Data from Savino et al suggested with a comparable formula that this kind of dietary intervention may be of benefit [11]. The formula in the study by Savino and the intervention formula in this trial both contain a pWH, reduced lactose and GOS as prebiotic.…”
Section: Introductionmentioning
confidence: 92%
“…The aim of this study was to evaluate the efficacy of a formula containing a partially hydrolyzed whey protein (pWH), reduced lactose content, the probiotic Bifidobacterium lactis BB12 and the prebiotic galacto-oligosaccharide (GOS) in formula fed infants suffering from IC. Data from Savino et al suggested with a comparable formula that this kind of dietary intervention may be of benefit [11]. The formula in the study by Savino and the intervention formula in this trial both contain a pWH, reduced lactose and GOS as prebiotic.…”
Section: Introductionmentioning
confidence: 92%
“…Physiological regurgitation should not be diagnosed in infants with vomiting and poor weight gain 22, 23.…”
Section: Management Of Regurgitationmentioning
confidence: 99%
“…Parents can be reassured that crying peaks at about 4–6 weeks after birth and then steadily diminishes until 12 weeks 4, 24. If there is no evidence of cows’ milk protein allergy or warning signs of organic disease, the feeding technique should be evaluated and the caregivers should be reassured and supported 22.…”
Section: Management Of Infantile Colicmentioning
confidence: 99%
See 2 more Smart Citations